2015
DOI: 10.1002/jemt.22579
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and morphological changes in human dentin after Er:YAGlaser irradiation: EDS and SEM analysis

Abstract: Sixty samples of human dentin were divided into six groups (n = 10) and were irradiated with Er:YAG laser at 100 mJ-19.9 J/cm(2), 150 mJ-29.8 J/cm(2), 100 mJ-35.3 J/cm(2), 150 mJ-53.0 J/cm(2), 200 mJ-70.7 J/cm(2), and 250 mJ-88.5 J/cm(2), respectively, at 7 Hz under a water spray. The atomic percentages of carbon, oxygen, magnesium, calcium, and phosphorus and the Ca-to-P molar ratio on the dentin were determined by energy dispersive X-ray spectroscopy. The morphological changes were observed using scanning el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Moreover, P amounts for these groups were significantly higher than the amount of Biflorid 10. This finding is in line with Contrera-Arriaga et al [45], who reported similar P amounts after Er:YAG laser irradiation. Mg concentration is 1% (wt) in dentin tissue.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, P amounts for these groups were significantly higher than the amount of Biflorid 10. This finding is in line with Contrera-Arriaga et al [45], who reported similar P amounts after Er:YAG laser irradiation. Mg concentration is 1% (wt) in dentin tissue.…”
Section: Discussionsupporting
confidence: 92%
“…Its mechanism in hard tissue ablation is the thermo-mechanical effect induced by the "micro-explosion" of water molecules (4). The sudden evaporation of bound water causes microexplosions that blast away tiny particles of bone tissue (5). Because of its many advantages, such as precise cut geometry, high bactericidal effect, reduced tissue bleeding, and less noise, vibration, and more discomfort for the patient than rotary instruments, the Er:YAG laser has been reported as suitable for use in clinical bone surgery (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies [11], the degradation of organic dentine and the changes in size and ultrastructure of apatite crystals due to laser irradiation substantially increase the acid-resistance of lased dentine. Additionally, it has been reported [12] [13] that Er:YAG laser irradiation reduces the carbon-to phosphorus ratio and leads to the formation of more stable and less acid-soluble compounds, thus reducing the susceptibility of dentine to acid attack. Therefore, it seems feasible that an etchant agent with stronger acid potential, such as 35% phosphoric acid, would remove the laser-modified dentine layer more efficiently than an etchant agent with weaker acid potential, such as the acidic monomer in self-etching primers.…”
Section: Introductionmentioning
confidence: 99%